Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengungkapan Wajib Laporan Keuangan Pemerintah Daerah - Winda Meiliza Putri; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to analyze the effect of local government characteristics on the level of mandatory disclosure of local government financial statements (LKPD) based on Government Accounting Standards. The sample in this study amounted to 57 District / City LKPDs in Indonesia in 2015-2017. The average level of mandatory disclosure of Regional Government Financial Reports is 61%. The size of the local government, the age of the regional government, the number of SKPD, the Dependency Level, the Regional financial independence ratio, and the Audit Opinion did not influence the level of mandatory disclosure of local government financial statements. While the wealth of the Regional Government has a positive and significant effect on the level of mandatory disclosure of local government financial statements.